Non Nosocomial Cardiac Arrest: Impact on Intensive care Units. Descriptive Study 1989-1992 - Vaghi, Massimo (1996)
Various studies slhow differences iii survival of patients who undernent CPR for non nosocomial cardiorespiratory arrest (CRA). Most patients die during CPR intent, many of the resuscitated patients die during intensive therapy after initial organic failures, and some survive with severe cerebral impaiment and high emotional, medical and social costs. ln this descriptive trial we retrospectively examined the «non nosoconfial CPR» phenonienon ocurred from 1989 till 1992, analizing data related to patients adinitted to the Emergeny Service (ES) with the diagnosis of CRA and who underwent CPR. We assessed the impact of this entity on Intensive Care Units (ICU and CCU) in relation to patient's condition at discharge and days of hospitalization. In addition, evolution of patients during   1992 was acquainted. We studied 210 patients, 55 of them attended during 1992. The average survival  in ES is  32% and increased from 28,6% to 36,4%. From 68 patients successfully reanimated by the Rapid Assistance.Service (RAS), 38% were admitted to UCC and 62 % to lCU. Twenty-nine  of 69 patients died in the intensive care unit (43%). Total survival for RAS has increased from 8% to 16 % (average 13,8%). Hospitalization days of patients that died in ICU usually less than patients with favourable evolution Survival of patients with ventricular fibrillation (VF) is 28%. Results obtained are not significatively different froni data encoutered in the literature.